Impact of exercise training on exercise tolerance, cardiac function and quality of life in individuals with heart failure and preserved ejection fraction: a systematic review and meta-analysis - Hu Li; Yingxue Liu; Yu Liu; Zhichao Xu; Pengchao Pan; Lijun Zeng (BMC Cardiovascular Disorders)
Abstract Background Heart failure with preserved ejection fraction (HFpEF) is increasingly prevalent and poses significant treatment challenges due to its complex pathophysiology. Exercise training has emerged as a promising non-pharmacological intervention to improve outcomes in HFpEF patients. This study aims to evaluate the effect of exercise training on exercise tolerance, cardiac function and quality of life in HFpEF patients. Method Through systematic review and meta-analysis, major databases were scoured for randomized controlled trials (RCTs) evaluating the influence of exercise training on HFpEF patients. Data on exercise tolerance, cardiac function parameters, and quality of life were extracted. The quality of the studies was assessed using the Cochrane Collaboration’s risk of bias tool. Statistical analyses were performed using Review Manager 5.4, with mean differences (MD) or standardized mean differences (SMD) and 95% confidence intervals (CIs) calculated for continuous variables. Results Seven RCTs encompassing 470 participants met the inclusion criteria. Exercise training significantly improved exercise tolerance as measured by the 6-Minute Walk Test (P < 0.01) and peak VO₂ (P = 0.03). No significant effects were observed on cardiac function parameters, including the E/A ratio, E/e’ ratio, and LVEF. Total quality of life was similar between exercise and control groups, but significantly enhanced in physical components about quality of life was observed in the exercise group (P = 0.03). There were no significant differences between high-intensity interval training (HIIT) and moderate continuous training (MCT) in improving exercise tolerance, cardiac function, or quality of life. Conclusion Exercise training effectively enhances exercise tolerance and physical quality of life in patients with HFpEF, without significantly impacting cardiac function parameters. HIIT and MCT has similar effect in HFpEF patients. These findings support the incorporation of exercise training into the management strategies for HFpEF patients to improve functional outcomes and quality of life.